Photocatalytic H2O2 production Systems: Design strategies and environmental applications - Chen, Zhong; Yao, Ducheng; Chu, Chengcheng; Mao, Shun (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Fundamental reaction processes in photocatalytic H2O2 production are introduced.•Recent advances of design strategies in improving the photocatalytic H2O2 production efficiency are reviewed.•Environmental applications of photocatalytic H2O2 production are discussed.•Prospects of photocatalytic H2O2 production and its future applications are provided. Hydrogen peroxide (H2O2) is an environmentally friendly versatile oxidant, which has been used in chemical industry, medical, energy, and environmental fields. Photocatalytic H2O2 production is a sustainable, safe, and green process; however, the high recombination of electron-hole pairs, low visible light utilization, and poor product selectivity still limit the practical applications of photocatalytic H2O2 production. Previous reviews on photocatalytic H2O2 generation focus more on the photocatalysts but less on the design strategy of the photocatalytic systems, which stems from the critical steps involving the photocatalytic process, i.e., light absorption, charge separation, and surface redox reaction. From this point of review, this review article introduces the strategies for improving the H2O2 production efficiency based on the above three critical processes. Moreover, the environmental applications of photocatalytic H2O2 generation including disinfection and pollutant degradation are discussed. The challenges and prospects in photocatalytic H2O2 production and its future environmental applications are also envisioned.